Implikasi Religius Magis Pengembangan Wisata di Kawasan Suci Pura Tanah Lot - I Putu Agus Aryatnaya Giri; I Made Girinata; I Ketut Wiratmaja (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
In line with the development of tourism in the sacred area of ​​Tanah Lot Temple, Pakraman Beraban Village, it is seen that the development of Hindu society in the level of lifestyle, culture, and social religion occurs dynamically in line with the development of global tourism. Based on the facts, space commodification can be identified.On the one hand commodification can produce material benefits, while on the other hand it can be a threat to the religious religiosity of the community and the sanctuary area of ​​Tanah Lot Temple which has the status of a heavenly heavenly temple. The sacred area of ​​Tanah Lot Temple as a cultural capital which is a tourist attraction in the development of tourism in the village of Berraman Beraban contains magical religious meaning. Conceptually this religious meaning reflects changes in cultural capital is expected not to have a negative impact on religious teachings that are believed by the manners of Desa Pakraman Beraban. It is hoped that tourism culture will not damage the culture of Pakraman Beraban Village which is imbued with Hinduism. Although tourism culture seems to be very prominent in the space of Desa Pakraman Beraban religiosity remains firmly rooted in the life of the Pakraman village based on tri hita karana. Therefore, the preservation of the existence of Hinduism also means the preservation of tourism sustainability in the village of Pakraman Beraban.